A retrospective study on the efficacy of integrating traditional Chinese medicine with Western medicine in the treatment of adult measles - Xiaoyan Liu; Zhongying Bao; Shuhong Duan; Jing Sun; Jie Zhang (Hereditas)
Abstract Objective Measles is a highly contagious, potentially fatal disease, and using western medicine for treating this disease showed some limits including the long period of treatment and some side effects. Of note, traditional Chinese medicine (TCM) exhibited advantages of treating measles in using alone or combing with western medication. However, little information on the clinical study on adjunctive efficacy of TCM on measles. Therefore, the objective of this study is to observe the adjunctive efficacy of TCM in the treatment of adult measles. Methods Ninety-one patients diagnosed with adult measles in our hospital were enrolled for this study. All of them underwent symptomatic treatment, nutritional support therapy, and ribavirin antiviral therapy. Loxoprofen was added to the treatment regime when the body temperature exceeded 38.5 °C. The patients were stratified into two groups based on the administration of TCM, comprising 49 individuals in the TCM group and 42 individuals in the control group. Patients in the TCM group voluntarily received the following TCM prescriptions: 15 g of Lonicerae Japonica, 15 g of Forsythiae Fructus, 15 g of Arnebiae Radix, 15 g of Cicadae Periostracum, 30 g of Phragmitis Rhizoma, 10 g of Anemarrhenae Rhizoma, 6 g of Glycyrrhizae Radix et Rhizoma and 30 g of Gypsum Fibrosum was administered to patients with high fever. Decoction: 1 dose daily for 5 days. The control group received treatment without the incorporation of TCM. Results In comparison to the control group, patients in the TCM group experienced a quicker resolution of clinical symptoms (P < 0.05) and a lower complication rate (P < 0.05). Conclusion The application of TCM in treating adult measles can shorten the duration of the disease, reduce the incidence of complications, and offers promise for wider clinical adoption and utilization.